Promoting Whole Health and Well-Being at Home: Veteran and Provider Perspectives on the Impact of Tele-Whole Health Services - Aishwarya Khanna BS; Eileen M. Dryden PhD; Rendelle E. Bolton MPH, MSW, MA; Juliet Wu BS; Stephanie L. Taylor PhD; Marla L. Clayman MPH, PhD; Chitra Anwar MA; Danna Kasom BS; Michael McGowan MA; Rashmi S. Mullur MD; Barbara G. Bokhour PhD; Justeen Hyde PhD (SAGE Publishing, 2022)
Background The Veterans Health Administration (VA) is undergoing a transformation in how healthcare is organized and provided. This transformation to a Whole Health System of Care encompasses the integration of complementary and integrative health services, education, and Whole Health coaching to develop Veterans' self-care skills. During the COVID-19 pandemic, these services were provided via telehealth (tele-WH). Objective We sought to understand Veteran and provider perspectives on how tele-WH impacts Veteran engagement in Whole Health-aligned services and the impact on their well-being. Methods Semi-structured interviews were conducted with 51 providers who delivered tele-WH at 10 VA Medical Centers (VAMCs) and 19 Veterans receiving tele-WH at 6 VAMCs. Participants were asked about their experiences with tele-WH, what they perceived to be the impact of tele-WH on Veterans, and their preferences moving forward. Interviews were transcribed, and a content analysis was performed using a rapid approach. Results We identified 3 major themes that describe the perceived impact of tele-WH on Veterans. These include: (1) increased use of Whole Health-aligned services; (2) deeper engagement with Whole-Health aligned services; and (3) improvements in social, psychological, and physical well-being. Conclusion Tele-WH is perceived to be a strong complement to in-person services and is a promising mechanism for improving engagement with Whole Health-aligned services and promoting Veteran well-being. Future research is needed to measure outcomes identified in this study and to support more equitable access to telehealth for all.